Paediatric Meningitis and Hearing Loss in a Developing Country: Exploring the Current Protocols Regarding Audiological Management Following Meningitis - Katijah, Khoza-Shangase (African Ethnomedicines Network, 2010)
The purpose of this study was to establish audiology referral protocols for post meningitis paediatric populations in two academic hospitals in Gauteng, South Africa. Specific objectives of this study included determining if audiological assessment referrals were made following infection; determining the time of referral post meningitis diagnosis; establishing what audiological assessments were conducted on this population, as well as determining any correlations between signs and symptoms of meningitis and referrals for audiology assessments. Medical records of 47 children admitted to hospital with a diagnosis of meningitis between the ages of birth and 6 years were reviewed following a retrospective record review design. Data relevant to the current study were obtained from hospital records and this was captured in a data spreadsheet. Both descriptive and inferential statistics were implemented in analysis of the data. Inferential statistics in the form of logistic regression analysis was used to establish any significant factor that may predict referral for audiological assessment. The findings indicated that almost half (40%) of the cases were not referred for audiological services. Of those cases referred for assessment, 89% were referred as in-patients before hospital discharge, with minimal referrals occurring after discharge from hospital. Screening, rather than diagnostic audiology measures were conducted on a majority of the cases. Logistic regression analysis identified fever as the only predictor variable (p<0.01) for audiological assessment referral. Results from this study highlight the need for the establishment of audiology referral protocols for paediatric meningitis populations to ensure that early identification and early intervention occurs.